2022
DOI: 10.3390/jcm11071797
|View full text |Cite
|
Sign up to set email alerts
|

Cranial Shape in Infants Aged One Month Can Predict the Severity of Deformational Plagiocephaly at the Age of Six Months

Abstract: In this study, we aimed to monitor changes in cranial shape using three-dimensional (3D) scanning to determine whether the severity of deformational plagiocephaly (DP) at the age of 6 months could be predicted at the age of 1 month. The cranial shape was measured at the ages of 1, 3, and 6 months (T1, T2, and T3, respectively) in 92 infants. We excluded those who received helmet treatment before T3. The cranial vault asymmetry index (CVAI) using 3D scanning was evaluated in all infants. DP was defined as a CVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Previous report shows that DP exacerbates until 3 months of age before spontaneously improving throughout the first 6 months of life. 10) We have also reported that helmet therapy could improve CA three times better than spontaneous recovery. 22) These facts could be important determinants in the decision-making process for the indications for helmet therapy for DP.…”
Section: Dp and Growth-related Parametersmentioning
confidence: 80%
See 4 more Smart Citations
“…Previous report shows that DP exacerbates until 3 months of age before spontaneously improving throughout the first 6 months of life. 10) We have also reported that helmet therapy could improve CA three times better than spontaneous recovery. 22) These facts could be important determinants in the decision-making process for the indications for helmet therapy for DP.…”
Section: Dp and Growth-related Parametersmentioning
confidence: 80%
“…However, because we excluded children with severe DP who were indicated for helmet therapy, future studies should include children with severe DP. In this study, we included six patients (6.8%) with severe DP with CVAI > 8.75% 10 ) at 6 months. Peterson et al compared DP infants with and without helmet therapy and reported no significant differences in final CrV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations